2014
DOI: 10.1186/1471-2407-14-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of phosphatidylinositol 4-kinase type IIIα is associated with undifferentiated status and poor prognosis of human hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a particularly severe disease characterized by a high rate of recurrence and death even after surgical resection. Molecular characterization of HCC helps refine prognosis and may facilitate the development of improved therapy. Phosphatidylinositol 4-kinases have recently been identified as cellular factors associated with cancer. Also, phosphatidylinositol 4-kinase type IIIα (PI4KA) is necessary for the propagation of the hepatitis C virus, a major etiological factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…Phosphatidylinositol 4-Kinase Alpha ( PI4KA ) catalyzes the first step of the biosynthesis of phosphatidylinositol 4,5-bisphosphate. It has been found to be overexpressed in hepatocarcinoma, showing a positive and significant correlation with expression of PCNA and KI67 proliferation markers and associated to a poor prognosis [41] . HECT Domain And RCC1-Like Domain-Containing Protein 2 ( HERC2 ) facilitates the assembly of the RNF8-UBC13 complex to recruit BRCA1 to DNA damaged sites, and it also plays a role in p53 oligomerization [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol 4-Kinase Alpha ( PI4KA ) catalyzes the first step of the biosynthesis of phosphatidylinositol 4,5-bisphosphate. It has been found to be overexpressed in hepatocarcinoma, showing a positive and significant correlation with expression of PCNA and KI67 proliferation markers and associated to a poor prognosis [41] . HECT Domain And RCC1-Like Domain-Containing Protein 2 ( HERC2 ) facilitates the assembly of the RNF8-UBC13 complex to recruit BRCA1 to DNA damaged sites, and it also plays a role in p53 oligomerization [42] .…”
Section: Discussionmentioning
confidence: 99%
“…All 40 genes, however, did not affect prognosis in patients with TP53 mutant cancer (Figure 6B , Supplementary Figure 1 ), demonstrating a dependence on TP53 mutational status. The genes selected using this method included NCOA3 [ 34 , 35 ], HOXA1 [ 36 ], FOLR1 [ 37 ], SOCS1 [ 38 ], and PIK4CA [ 39 ], which showed similar expression patterns related to survival in patients with cancer. This result suggested that our method was a relatively simple method for identification of genes functionally associated with the p53 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity ratios for PIK3CA and PI4KA were nearly equal to those for PTEN. Dysregulation of PIK3CA and PI4KA is commonly found in HNSCC [46] and hepatocellular carcinoma [43], respectively.…”
Section: Detecting One-hit Oncogenementioning
confidence: 99%